Plastic Biliary Stent Occlusion: Factors Involved and Possible Preventive Approaches - Donelli, Gianfranco (© 2007. Clinical Medicine & Research, 2007)
Endoscopic biliary stenting is today the most common palliative treatment for patients suffering from obstructive jaundice associated with malignant hepatobiliary tumors or benign strictures. However, recurrent jaundice, with or without cholangitis, is a major complication of a biliary endoprosthesis insertion. Thus, stent removal and replacement with a new one frequently occurs as a consequence of device blockage caused by microbial biofilm growth and biliary sludge accumulation in the lumen. Factors and mechanisms involved in plastic stent clogging arising from epidemiological, clinical and experimental data, as well as the possible strategies to prevent biliary stent failure, will be reviewed and discussed.